In vitro extracellular replication of Wolbachia endobacteria - Behrmann, Lara Vanessa; Meier, Kirstin; Vollmer, Jennifer; Chiedu, Chukwuebuka Chibuzo; Schiefer, Andrea; Hoerauf, Achim; Pfarr, Kenneth (Frontiers in Microbiology, 2024)
Obligate intracellular endobacteria of the genus Wolbachia are widespread in arthropods and several filarial nematodes. Control programs for vector-borne diseases (dengue, Zika, malaria) and antifilarial therapy with antibiotics are based on this important endosymbiont. Investigating Wolbachia, however, is impeded by the need for host cells. In this study, the requirements for Wolbachia wAlbB growth in a host cell-free in vitro culture system were characterized via qPCRs. A cell lysate fraction from Aedes albopictus C6/36 insect cells containing cell membranes and medium with fetal bovine serum were identified as requisite for cell-free replication of Wolbachia. Supplementation with the membrane fraction of insect cell lysate increased extracellular Wolbachia replication by 4.2-fold. Replication rates in the insect cell-free culture were lower compared to Wolbachia grown inside insect cells. However, the endobacteria were able to replicate for up to 12 days and to infect uninfected C6/36 cells. Cell-free Wolbachia treated with the lipid II biosynthesis inhibitor fosfomycin had an enlarged phenotype, seen previously for intracellular Wolbachia in C6/36 cells, indicating that the bacteria were unable to divide. In conclusion, we have developed a cell-free culture system in which Wolbachia replicate for up to 12 days, providing an in vitro tool to elucidate the biology of these endobacteria, e.g., cell division by using compounds that may not enter the C6/36 cells. A better understanding of Wolbachia biology, and in particular host-symbiont interactions, is key to the use of Wolbachia in vector control programs and to future drug development against filarial diseases.